Mobilization Under Threat: Emotional Appeals and Pro-Opposition Political Participation Online - Young, Lauren E. (Political behavior, 2023)
Large numbers of people living under authoritarian governments participate in pro-opposition politics despite sometimes significant risks. Increasing amounts of this political participation are taking place and being organized online. Do emotions play a causal role in inducing pro-opposition participation in authoritarian regimes? Can emotions that mobilize participation be spread via social media? Through an experiment carried out by an opposition party in Zimbabwe, I test whether campaign appeals to opposition supporters’ emotions affect their level of political participation in online pro-opposition discussions. I find that across two different issue areas, randomly assigned anger appeals increase participation on average by 0.4 standard deviations more than enthusiasm appeals with the same informational content. In real terms, this represents between 30% and 170% more participation in the groups assigned to the anger appeals across four different measures of participation. There is little evidence that these effects are stronger in areas with less poverty or that have historically been affected by more violence, or when coupled with messages emphasizing personal power. These results suggest that anger appeals that highlight economic grievances can be an important force for mobilizing online political participation in repressive environments.